Relationship between incoterms choices, selection factors and export performance: A case of manufacturing companies in Malaysia - Leong, Ying Szu (2014)
The present study has three major objectives: (1) To determine the most frequently used Incoterms 2010 among manufacturers in Malaysia. (2) To identify the factors that influence the Incoterms selection by the manufacturers. (3) To examine the relationship between the selection factors, Incoterms choice and export performance. This study is a quantitative research and was conducted in Malaysia and the sample was selected from the Federation of Malaysian Manufacturers (FMM). A total of 335 questionnaires were distributed and 60 questionnaires were returned with complete answer. The valid response is 17.91%. The collected data was analyzed through reliability analysis, which is Cronbach’s Alpha, descriptive analysis and correlation analysis. EXPERF tools developed by Zou in 1998 uses three dimensions to evaluate the export performance, which is through financial performance, strategic performance and export performance which is a perceived performance. The results showed that (1) FOB is the most frequently used Incoterms in Malaysia. (2) There are factors influencing the Incoterms selection including new added factors. (3) There are significant relationships between selection factors with Incoterms selection, and selection factors with export performance. In conclusion, this study focuses on factors influencing the choices of Incoterms and its impact on the export performance. The possible neglected factors such as intangible units, employee behaviours, conducted study overseas and et cetera.